2015
DOI: 10.1371/journal.pone.0117086
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Negativity of Age Stereotypes across 200 Years: Evidence from a Database of 400 Million Words

Abstract: Scholars argue about whether age stereotypes (beliefs about old people) are becoming more negative or positive over time. No previous study has systematically tested the trend of age stereotypes over more than 20 years, due to lack of suitable data. Our aim was to fill this gap by investigating whether age stereotypes have changed over the last two centuries and, if so, what may be associated with this change. We hypothesized that age stereotypes have increased in negativity due, in part, to the increasing med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 13 publications
9
132
1
6
Order By: Relevance
“…This is as expected, as a recent study found that age stereotypes became significantly worse over the span of two centuries[19]. All of this is epitomized in the fact that most would rather not work with older people both before and after the care internship.…”
Section: Discussionsupporting
confidence: 84%
“…This is as expected, as a recent study found that age stereotypes became significantly worse over the span of two centuries[19]. All of this is epitomized in the fact that most would rather not work with older people both before and after the care internship.…”
Section: Discussionsupporting
confidence: 84%
“…The study found that negativity towards older adults has grown in step with their relative share within society, presumably due to concerns of the younger generation that older adults act as a drain on economic resources (Ng et al 2015). Complicating matters still, these concerns are not completely unfounded; with fertility rates falling and lifespans extending in recent years, the retired population is growing larger and larger in proportion to the employed sector, and it is expected that care for older adults -formal and informal -will impose a heavy cost on society (Suzman and Beard 2011).…”
Section: Ageismmentioning
confidence: 93%
“…A recent large-scale linguistic analysis encompassing two centuries of written American English has found that stereotypes of older adults have grown increasingly negative over the years (having started out slightly positive in the 1800s; Ng et al 2015). The study found that negativity towards older adults has grown in step with their relative share within society, presumably due to concerns of the younger generation that older adults act as a drain on economic resources (Ng et al 2015).…”
Section: Ageismmentioning
confidence: 96%
“…Among medical providers, Gunderson and colleagues (Gunderson et al 2005) found that rurally-based physicians in the U.S. endorsed more negative views of "nursing home patients" compared to typical "older" patients, in terms of patients' ability to change health behaviors and to learn new health-related information, their ability to offer important input during a medical visit, and their personality traits (e.g., "less warm and accepting"). Healthism may be related to the increasing "medicalization" of old age in Western societies identified by some scholars (Ng et al 2015). Increased focus on the medical aspects of being old -to the exclusion of other dimensions of older age -is reflected at the level of policy and reimbursement in the geriatric health care setting, and has a clear impact on provider choices, service availability, and quality of care (Binney et al 1990).…”
Section: Factors Associated With Ageism In the Medical Settingmentioning
confidence: 99%
“…Increased focus on the medical aspects of being old -to the exclusion of other dimensions of older age -is reflected at the level of policy and reimbursement in the geriatric health care setting, and has a clear impact on provider choices, service availability, and quality of care (Binney et al 1990). A recent sociological study of changes in culture-based age stereotypes appearing in print over the past 200 years in the USA found an increasing association over time between the mention of an older adult and references to the medical status of that person, using words such as "sickness" or "stamina" (Ng et al 2015). This increasing medicalization of old age was associated with increasingly negative age stereotypes, leading the authors to conclude that this increasing negativity toward older adults is systemic and pervasive throughout the culture.…”
Section: Factors Associated With Ageism In the Medical Settingmentioning
confidence: 99%